Efforts To Optimize Loading and Unloading Equipment - Setiyantara, Yudhi; Astriawati, Ningrum; Kusuma, Ade Chandra; Widyanto, Handoyo; Kristianto, Lukas; Kusuma, Arif Agus Budiawan (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
The purpose of this study is to determine the efforts made to optimize loading and unloading equipment to facilitate loading and unloading in MV. Isa Golden. The method used in this study is qualitative descriptive. The results of the study include efforts made to optimize the maintenance of loading and unloading equipment by planning loading and unloading maintenance on a scheduled basis by following the maintenance checklist that has been determined by the ship management, evaluating at safety meetings or deck meetings to provide solutions to problems if found and provide answers or solutions to each problem, Make coordination in parts of the organization in dividing 2 (two) groups in loading and unloading equipment maintenance activities or other maintenance so that it can run well following the job description. Mualim I is obliged to compile crane spare parts to make it easier to supervise spare parts that are not available. View lists of equipment and spare parts that expire and make replacements if there is equipment that expires or is used by making and submitting a list of spare parts requests to the company